2022
DOI: 10.1111/jocd.15394
|View full text |Cite
|
Sign up to set email alerts
|

Decellularized human amniotic membrane engraftment in combination with adipose‐derived stem cells transplantation, synergistically improved diabetic wound healing

Abstract: Background One of the most important and common complications of diabetes is a disorder and defect in diabetic wound healing. Aims The aim of present study was to investigate the synergistic effects of decellularized human amniotic membrane (dHAM) engraftment and adipose‐derived stem cells (ADSs) transplantation in the healing of delayed and ischemic diabetic wound. Methods Sixty diabetic male rats were randomly divided into four groups (n = 15), including untreated (Control) group, engraftment by dHAM (dHAM) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Earlier studies have reported that preserving the ECM components of decellularized bio-scaffolds provides a suitable microenvironment for allogeneic cells for attachment, proliferation, and differentiation along various lineages. 59,60 Moreover, numerous studies have suggested the combined use of MSCs with a D-hAM, [61][62][63] (i) to enhance healing capacity by accelerating the reepithelialization, modulating inflammation, promoting granulation tissue formation and regulating remodeling of ECM 64 (ii) to increase its anti-infective effects resulting from the increased production of anti-inflammatory proteins like interleukin-10 (IL-10) and M2 macrophages and the reduced expression of pro-inflammatory cytokines like interleukin-1 (IL-1), interleukin-6 (IL-6), and transforming growth factor-β (TGF-β) 65 (iii) to induce and maintain multilineage differentiation in response to various stimulus from three dimensional system, 66 and (iv)to direct angiogenesis by secreting pro-angiogenic factors such as VEGF, insulin like growth factor (IGF), and angiogenin. 67 Hence, we hypothesized that D-hAM would support the attachment and proliferation of hUC-MSC while proving to be a biocompatible scaffold for future tissue engineering and regenerative applications.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have reported that preserving the ECM components of decellularized bio-scaffolds provides a suitable microenvironment for allogeneic cells for attachment, proliferation, and differentiation along various lineages. 59,60 Moreover, numerous studies have suggested the combined use of MSCs with a D-hAM, [61][62][63] (i) to enhance healing capacity by accelerating the reepithelialization, modulating inflammation, promoting granulation tissue formation and regulating remodeling of ECM 64 (ii) to increase its anti-infective effects resulting from the increased production of anti-inflammatory proteins like interleukin-10 (IL-10) and M2 macrophages and the reduced expression of pro-inflammatory cytokines like interleukin-1 (IL-1), interleukin-6 (IL-6), and transforming growth factor-β (TGF-β) 65 (iii) to induce and maintain multilineage differentiation in response to various stimulus from three dimensional system, 66 and (iv)to direct angiogenesis by secreting pro-angiogenic factors such as VEGF, insulin like growth factor (IGF), and angiogenin. 67 Hence, we hypothesized that D-hAM would support the attachment and proliferation of hUC-MSC while proving to be a biocompatible scaffold for future tissue engineering and regenerative applications.…”
Section: Discussionmentioning
confidence: 99%